Effects of hydrophobic coating on properties of hydrochar produced at different temperatures: Specific surface area and oxygen-containing functional groups. (November 2022) - Fan, Jianping; Li, Fangfang; Fang, Dexin; Chen, Quanzhou; Chen, Qingkong; Wang, Huan; Pan, Bo
Graphical abstract: Highlights: Hydrophobic coating formed on hydrochar surfaces. Hydrophobic coating properties differed with different carbonization temperatures. Hydrophobic coatings produced above 180 °C had much palmitic acid. Hydrochar specific surface area increased 323.8% after hydrophobic coating removal. Oxygen-containing functional groups increased after hydrophobic coating removal. Abstract: Hydrochar's specific surface area (SSA) is important in environmental remediation; however, a hydrophobic coating formed on hydrochar creates a physical barrier that reduces that SSA. The formation and composition of the hydrophobic coating and its effects on hydrochar properties are unclear. In this study, hydrochar was produced from Chinese fan palm ( Livistona chinensis ) leaves at different temperatures. The resulting hydrophobic coatings were investigated by in situ characterization and then extracted with acetone for composition identification. Additionally, hydrochar properties were compared before and after hydrophobic coating removal. The results showed that the hydrophobic coating of the hydrochar produced at 180 °C was the insoluble cuticle layer of raw biomass, while the hydrophobic coatings formed above 180 °C were the depolymerization products of cutin. For the hydrochar above 180 °C, especially at 260 °C, the removal of the hydrophobic coating from hydrochar increased both its SSA and its oxygen-containing functional groups.